A developmental arrest? Interruption and identity in adolescent chronic pain. (September 2018) - Jordan, Abbie; Noel, Melanie; Caes, Line; Connell, Hannah; Gauntlett-Gilbert, Jeremy
Abstract: Introduction: Although the pediatric pain literature has explored the role of developmental factors in young children's acute pain, relatively less is known about specific developmental challenges in adolescents with chronic pain. Objectives: To meet this knowledge gap, this study sought to adopt an idiographic phenomenological approach to examine how adolescents make sense of their own development in the context of living with chronic pain. Methods: Semistructured interviews were conducted with ten adolescents (12–17 years; 7 females) recruited from a tertiary care pain treatment programme. Interview data were transcribed verbatim and analysed using Interpretative Phenomenological Analysis. Results: Study findings identified 2 themes: "An externally imposed lens on identity" and "Paradoxes of developmental progress." The first theme highlighted an understanding of how adolescent identity is perceived. Some adolescents perceived identity as distinct from pain, whereas others perceived identity as part of their chronic pain condition. This theme also detailed how identity was negotiated by adolescents and others through engagement with valued activities. The second theme represented an understanding of how chronic pain disrupts and alters adolescent developmental trajectories at an individual level, suggesting possibilities of enhanced and delayed trajectories. Enhanced trajectories were associated with increased management of emotionally difficult situations and resulted in mastery of complex interpersonal skills. Conclusion: Findings provided a nuanced understanding of developmental progress in the context of adolescent chronic pain and suggested challenges with drawing normative comparisons. Future research could extend findings by adopting a longitudinal approach to studying adolescent development and eliciting accounts from broader social groups.